Multiple benefits of manure : The key to maintenance of soil fertility and restoration of depleted sandy soils on African smallholder farms - Zingore, Shamie; Delve, Robert J.; Nyamangara, Justice; Giller, Kenneth E. (Springer, 2008)
Manure is a key nutrient resource on smallholder farms in the tropics, especially on poorly buffered sandy soils, due to its multiple benefits for soil fertility. Farmers preferentially apply manure to fields closest to homesteads (homefields), which are more fertile than fields further away (outfields). A three-year experiment was established on homefields and outfields on sandy and clayey soils to assess the effects of mineral nitrogen (N) fertilizer application in combination with manure or mineral phosphorus (P) on maize yields and soil chemical properties. Significant maize responses to application of N and manure were observed on all fields except the depleted sandy outfield. Large amounts of manure (17 t ha?1 year?1) were required to significantly increase soil organic carbon (SOC), pH, available P, and base saturation, and restore productivity of the depleted sandy outfield. Sole N as ammonium nitrate (100 kg N ha?1) or in combination with single superphosphate led to acidification of the sandy soils, with a decrease of up to 0.8 pH units after three seasons. In a greenhouse experiment, N and calcium (Ca) were identified as deficient in the sandy homefield, while N, P, Ca, and zinc (Zn) were deficient or low on the sandy outfield. The deficiencies of Ca and Zn were alleviated by the addition of manure. This study highlights the essential role of manure in sustaining and replenishing soil fertility on smallholder farms through its multiple effects, although it should be used in combination with N mineral fertilizers due to its low capacity to supply N.